Response Surface Methodology Application in the Optimization of Cd(II) Removal from Produced Water by Chitosan - Zaman, H.G. (Institute of Electrical and Electronics Engineers Inc., 2020)
Produced water is a significant waste stream because of its changing characteristics from well to well. It is on the increase and requires remediation. Treating produced water with adsorption provides better performance for heavy metals when compared to other techniques. The main objective of this study was to investigate and optimize the adsorption process in removing toxic metal using the CCD (central composite design) which is RSM (response surface methodology) module in the software Design-ExpertÂ®. The effect of adsorbent dosage, contact time, and pH were analyzed empirically and optimized successfully by RSM. The presence of Cd (II) in produced water represents a major environmental and human health risk due to its high toxicity and bioaccumulation potential. Statistically significant quadratic polynomial for Cd (II) was obtained via regression analysis R2 (0.94). The highest removal efficiency 88.45 was achieved under the optimized conditions at pH 6, dosage 6 g/L, contact time 60 minutes, and initial concentration of 6ppm. Â© 2020 IEEE.